2006
DOI: 10.1103/physreva.73.051601
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a supersolid in cold-atom optical lattices

Abstract: We suggest a technique for the observation of a predicted supersolid phase in extended Bose-Hubbard models which are potentially realizable in cold atom optical lattice systems. In particular, we discuss important subtleties arising from the existence of the trapping potential which leads to an externally imposed (as opposed to spontaneous) breaking of translational invariance. We show, by carefully including the trapping potential in our theoretical formalism, that noise correlations could prove instrumental … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 29 publications
(30 reference statements)
4
99
0
Order By: Relevance
“…For the soft-core model, both Gutzwiller approximations [29,30] and QMC simulations [25,26] have shown that checker-board SS phases can be stable against the PS. However, the details of the two types of study differ.…”
Section: Introductionmentioning
confidence: 99%
“…For the soft-core model, both Gutzwiller approximations [29,30] and QMC simulations [25,26] have shown that checker-board SS phases can be stable against the PS. However, the details of the two types of study differ.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these aspects have attracted much attention and have lead to a series of predictions for novel e ects and quantum phases that could be realized with ultracold atoms in higher-lying orbitals. These include the generation of novel multi-avor and multi-orbital systems [3,4,5], supersolid quantum phases in cubic lattices [6,7], quantum stripe ordering in triangular lattices [8] or Wigner crystallization in honeycomb lattices [9]. An essential experimental question is however, how such systems could be prepared and whether they are stable.…”
mentioning
confidence: 99%
“…The possibility to extract information about the quantum statistics and the coherence, paved by the HBT experience, conjugated with the capabilities of deriving the temperature and the spatial order [7], contributed to make this technique one of the most powerful to probe atomic systems. The quest to understand the behavior of more and more complex samples suggests its application to the study of strongly interacting 1D gases [8,9], disordered [10] and supersolid phases [11] and to identify non trivial excitations [12]. While first order correlations are often accessible via interference experiments, higher order correlations require in general the recording of density or atom number fluctuations by a probe sensitive enough to detect single particles (counting techniques) or, at least, atomic shot-noise (absorption imaging).…”
mentioning
confidence: 99%